2006
DOI: 10.1038/nprot.2006.251
|View full text |Cite
|
Sign up to set email alerts
|

Microcontact printing of axon guidance molecules for generation of graded patterns

Abstract: Microcontact printing (microCP) of proteins has been successfully used for patterning surfaces in various contexts. Here we describe a simple 'lift-off' method to print precise patterns of axon guidance molecules, which are used as substrate for growing chick retinal ganglion cell (RGC) axons. Briefly, the etched pattern of a silicon master is transferred to a protein-coated silicone cuboid (made from polydimethylsiloxane, PDMS), which is then used as a stamp on a glass coverslip. RGC explants are placed adjac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
128
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(130 citation statements)
references
References 23 publications
1
128
0
1
Order By: Relevance
“…Here we developed a novel micro-contact printing strategy 30 to study local effects of the laminin-332 containing matrix. We showed that RA-mechanosensitive currents in the same cell are only suppressed in neurites on a laminin-332 stripe, but not on the control laminin stripe.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Here we developed a novel micro-contact printing strategy 30 to study local effects of the laminin-332 containing matrix. We showed that RA-mechanosensitive currents in the same cell are only suppressed in neurites on a laminin-332 stripe, but not on the control laminin stripe.…”
Section: Discussionmentioning
confidence: 99%
“…To further examine the mechanism of action of laminin-332 we applied the technique of micro-contact printing of substrate proteins [30][31] . We generated cross-hatched grid patterns with laminin stripes in one direction crossed with stripes of either laminin alone or laminin mixed with laminin-332 at 90 o to the laminin stripe (laminin-332 henceforth always refers to a mix of laminin: 20 μg/ml; laminin-332: 1.33 μg/ml; Molar ratio 15:1) (Fig.…”
Section: Laminin-332 Acts Locally Not Globallymentioning
confidence: 99%
See 2 more Smart Citations
“…These zig-zag stripes are valuable when analyzing cell behavior and signal-transduction events at substrate borders, where, for example, one part of a cell is adhering to a laminin substrate and the other part is contacting a substrate of different molecular nature 30 . Also, a novel technique allowing for microcontact printing of proteins on surfaces has been reported and offers a versatile tool to study the behavior of, for example, navigating growth cones in gradients of axon guidance cues 31 .…”
Section: Introductionmentioning
confidence: 99%